2016
DOI: 10.5194/acp-16-277-2016
|View full text |Cite
|
Sign up to set email alerts
|

Plant surface reactions: an opportunistic ozone defence mechanism impacting atmospheric chemistry

Abstract: Abstract. Elevated tropospheric ozone concentrations are considered a toxic threat to plants, responsible for global crop losses with associated economic costs of several billion dollars per year. Plant injuries have been linked to the uptake of ozone through stomatal pores and oxidative damage of the internal leaf tissue. But a striking question remains: can surface reactions limit the stomatal uptake of ozone and therefore reduce its detrimental effects to plants?In this laboratory study we could show that s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 87 publications
3
86
0
Order By: Relevance
“…As observed in Fig. 14, the value of RH crit , the humidity level where the formation of the leaf surface water film starts, was found at 60 %. However, Jud et al (2016) observed a contribution of semi-volatile organic compounds, in this case diterpenes of Nicotiana tabacum, to non-stomatal sinks of O 3 . These observations demonstrated that special structures or organs can exist on the plant surface as in the case of glandular trichomes of Nicotiana tabacum, which may release stored volatile organic compounds impacting gas phase chemistry.…”
Section: Flux Measurements Under Laboratory Conditionsmentioning
confidence: 95%
“…As observed in Fig. 14, the value of RH crit , the humidity level where the formation of the leaf surface water film starts, was found at 60 %. However, Jud et al (2016) observed a contribution of semi-volatile organic compounds, in this case diterpenes of Nicotiana tabacum, to non-stomatal sinks of O 3 . These observations demonstrated that special structures or organs can exist on the plant surface as in the case of glandular trichomes of Nicotiana tabacum, which may release stored volatile organic compounds impacting gas phase chemistry.…”
Section: Flux Measurements Under Laboratory Conditionsmentioning
confidence: 95%
“…Glandular trichomes, which store and secrete various secondary metabolites such as flavonoids, monoterpenes, or sesquiterpene lactones, are widely distributed on leaf surfaces and may contribute significantly to defence against diverse biotic and environmental challenges (Agati, Azzarello, Pollastri, & Tattini, ; Amme et al, ; Ehleringer, Björkman, & Mooney, ; Fahn & Shimony, ; Heinrich, Pfeifhofer, Stabentheiner, & Sawidis, ; Huci, Beversdorf, & McKersie, ; Jud et al, ; Kostina, Wulff, & Julkunen‐Tiitto, ; Lihavainen et al, ; Paoletti, Seufert, Della, & Thomsen, ; Peiffer, Tooker, Luthe, & Felton, ; Rieseberg, Soltis, & Arnold, ; Thitz et al, ; Wagner, ). Two major types of glandular trichomes, peltate and capitate, have been discerned.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that reactions between O 3 and organic surfaces (i.e., soil, organic films) could be one non-photochemical surface-level source of alkanoic acids near the site, though unlikely to account for the entire source. Reactions of O 3 on organic surfaces such as organic films (Donaldson et al, 2005), plant surfaces (Cape et al, 2009;Jud et al, 2016), and human skin (Liu et al, 2016(Liu et al, , 2017 have been reported previously. Soil organic matter and organic films are often rich in alkenes (Vancampenhout et al, 2009;Donaldson et al, 2005;Simpson et al, 2006), which undergo ozonolysis reactions in the presence of O 3 (Criegee, 1975;Wolff et al, 1997).…”
Section: Alkanoic Acidsmentioning
confidence: 99%